(3GdeTcdGJ GdJQHhjI hYdGbJgG HGfNaGV GdQVG GdhXjaj hGdCOGA GdJOQjSj dOi eYdej GdeQMdI GdGHJOGFjI aj GdJYdje GdQSej hGdNGU aj bVGA YcGQ(B.s - (3GdQaGYj, djGd YHO GdSdGes ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdBOGHs, 2014)
(3gOaJ GdOQGSI GdMGdjI ddHMK Yf eUGOQ GdeTcdGJ GdJQHhjI hOQGSI JCKjQgG Ydi QVG GdeYde GdhXjaj hCOGFg GdJOQjSj eY ELQGA ebGQfI Ydi eSJhi gPg GdeTcdGJ JHYG deJZjQ GdLfS, fhY GdJYdje (B((3QSej hNGU(B) (3hGdeGOI GdJYdjejI (B((3dZI YQHjI, dZI aQfSjI, GLJeGYjGJ, QjGVjGJ hYdhe(B). (3Jqe GNJjGQ YjfI GdOQGSI ef eOGQS YcGQ GdGHJOGFjI GdQSejI hGdNGUI HGdWQjbI GdWHbjI GdYThGFjI, hgj echfI ef aFJjf(B: (3YjfI eeKdI ddeLJeY GdCUdj HfSHI (B20% (3bhGegG (B1526 (3eYdekG HhGbY (B1063 (3ef GdJYdje GdQSej (B(372 (3PchQ h(B691 (3EfGK(B) (3h(B463 (3eYdekG ef GdJYdje GdNGU (B(190 (3PchQ h(B273 (3EfGK(B) (3hCNQi aQYjI ecqhfI ef (B200 (3eYde; (B117 (3ef GdJYdje GdQSej (B(41 (3PchQ h(B76 (3EfGK(B) (3h(B83 (3ef GdJYdje GdNGU (B(33 (3PchQ h(B50 (3EfGK(B). (3ESJNOeJ aj GdOQGSI JbfjI GdebGHdI GdTNUjI hKdGKI ebGjjS Je GdJCcO ef KHGJgG hUObgG gj(B: (3ESJHGfI GdeTcdGJ GdJQHhjI, ebjGS GdQVG GdhXjaj, hbGFeI GdJbOjQ dCOGA GdeYde ef bHd GdWdGH(B. (3hbO cTaJ GdfJGFL GdEMUGFjI Yf hLhO eYGfGI eYqdej eOGQS YcGQ GdGHJOGFjI ef eTcdGJ eJfhYI(B: (3efgG eG HOG Ydi OQLI cHjQI eKd(B: (3eTcdGJ XQha GdYed GdeGOjI (B((3ShA GdeHGfj GdeOQSjI(B)(3, hLhO YOO cHjQ ef GdJdGePI aj GdUa hYOe GdGdJRGe HGdhGLHGJ GdeOQSjI, hCNQi HOJ HOQLI eJhSWI gj(B: (3ZehV hUQGY GdOhQ GdhXjaj, eTcdGJ eY GdEOGQI GdeOQSjI(B. (3hCNQi HOJ Ydi OQLI eJhSWI eKd(B: (3ZehV hUQGY GdOhQ GdhXjaj, eTcdGJ eY GdEOGQI GdeOQSjI, fbU GdhSGFd GdJQHhjI, eTcdGJ aj GdJYGed eY ChdjGA CehQ GdWdHI, YHA GdYed GdRGFO hYOe JMbjb hXjaI GdJYdje eWGeM hJhbYGJ GdeYde(B. (3hbO cTaJ fJGFL GdOQGSI Ydi eSJhi OQGSI GdaQhb, hLhO aQhb OGdI Hjf YjfJj GdJYdje GdQSej hGdNGU Ydi eSJhi GdeTcdGJ GdJQHhjI dUGdM eYdej GdJYdje GdQSej hYdi eSJhi GdOQLI GdcdjIdebjGS GdQVG GdhXjaj hcGaI eLGdGJg dUGdM eYdej GdJYdje GdNGU aj Mjf de Jcf GdaQhb OGdI HjfgeG Ydi eSJhi bGFeI JbOjQ GdCOGA(B. (3HNUhU eJZjQ LfS GdeYde, JHjf YOe hLhO aQhb OGdI Hjf eJhSW OQLGJ GdeYdejf heJhSW OQLGJ GdeYdeGJ Ydi eSJhi GdOQLI GdcdjI dGSJHGfI GdeTcdGJ GdJQHhjI hGdOQLI GdcdjI debjGS GdQVG GdhXjaj hhLhO aQhb OGdI EMUGFjG HjfgeG Ydi eSJhi GdOQLI GdcdjI dbGFeI JbOjQ COGA GdeYde hcGaI eLGdGJgG dUGdM GdeYdeGJ(B. (3Ydi eSJhi GdeGOI GdJYdjejI, JHjf hLhO aQhb OGdI EMUGFjG Hjf GdeLehYGJ GdJYdjejI GdNeS (B((3dZI YQHjI, dZI aQfSjI, GLJeGYjGJ, QjGVjGJ hYdhe(B) (3Ydi eSJhi GdOQLI GdcdjI dbGFeI JbOjQ COGA GdeYde abW MjK GQJaY eSJhi COGA eYqdej GddZI GdaQfSjI GdJOQjSj Yf eSJhi RedGFge eYdej GddZI GdYQHjI, GdGLJeGYjGJ, GdYdhe hGdQjGVjGJ(B.s
(3GdfhY (B: (3CWQhMIs
Keywords: Cycle primaire; Elementary Education; Job Satisfaction; Satisfaction professionnelle; (3GdQVi GdhXjajs; (3GdeQMdI GdGHJOGFjIs